Alcohol‐Induced Changes in Opioid Peptide Levels in Adolescent Rats Are Dependent on Housing Conditions. (16th December 2014) - Palm, Sara; Nylander, Ingrid
Abstract : Background: Endogenous opioids are implicated in the mechanism of action of alcohol and alcohol affects opioids in a number of brain areas, although little is known about alcohol's effects on opioids in the adolescent brain. One concern, in particular when studying young animals, is that alcohol intake models often are based on single housing that may result in alcohol effects confounded by the lack of social interactions. The aim of this study was to investigate short‐ and long‐term alcohol effects on opioids and the influence of housing conditions on these effects. Methods: In the first part, opioid peptide levels were measured after one 24‐hour session of single housing and 2‐hour voluntary alcohol intake in adolescent and adult rats. In the second part, a model with a cage divider inserted during 2‐hour drinking sessions was tested and the effects on opioids were examined after 6 weeks of adolescent voluntary intake in single‐and pair‐housed rats, respectively. Results: The effects of single housing were age specific and affected Met‐enkephalin‐Arg 6 Phe 7 (MEAP) in particular. In adolescent rats, it was difficult to distinguish between effects induced by alcohol and single housing, whereas alcohol‐specific effects were seen in dynorphin B (DYNB), beta‐endorphin (BEND), and MEAP levels in adults. Voluntary drinking affected several brain areas and the majority of alcohol‐induced effects were not dependent on housing. However, alcohol effects on DYNB and BEND in the amygdala were dependent on housing. Housing alone affected MEAP in the cingulate cortex. Conclusions: Age‐specific housing‐ and alcohol‐induced effects on opioids were found. In addition, prolonged voluntary alcohol intake under different housing conditions produced several alcohol‐induced effects independent of housing. However, housing‐dependent effects were found in areas implicated in stress, emotionality, and alcohol use disorder. Housing condition and age may therefore affect the reasons and underlying mechanisms for drinking and could potentially affect the outcome of a number of end points in research on alcohol intake.